MENINGKATKAN KETERAMPILAN BERTANYA PADA MURID KELAS IV SEKOLAH DASAR MELALUI METODE QUESTION STUDENT HAVE (QSH) - Riris Ristanti, Arfi; Farida Nur Kumala (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study was prompted by the low level of questioning skills among fourth-grade elementary school students. These poor questioning skills stem from the predominance of one-way, teacher-centered instruction; furthermore, students’ lack of self-confidence is also a contributing factor. Data from the pre-cycle phase showed that only 25.93% of students (7 out of 27 children) participated actively, while the remaining 74.07% (20 children) tended to be passive. To address this dynamic, the researcher aimed to improve students’ questioning skills through the implementation of the “Questions Students Have” (QSH) learning method. The methodology used was Classroom Action Research (CAR), conducted over two cycles and involving 27 students as formal subjects. Data were collected through observation, diagnostic tests, and field notes, which were subsequently analyzed using qualitative and quantitative descriptive statistical techniques. The research results demonstrated a significant improvement in students’ questioning skills. From the initial condition (pre-cycle) through Cycle I, there was a 34.05% increase, with a classical percentage of 62.96%. To maximize these results, corrective actions were continued in Cycle II. In this final stage, the students’ mastery rate rose again by 37.04%, successfully enabling all research subjects to achieve the target of 100% classical mastery. Thus, the application of the “Question Student Have” (QSH) method is highly effective in creating a comfortable and conducive learning environment.